1986
DOI: 10.1017/s0022112086002574
|View full text |Cite
|
Sign up to set email alerts
|

Network models for two-phase flow in porous media Part 1. Immiscible microdisplacement of non-wetting fluids

Abstract: A theoretical simulator of immiscible displacement of a non-wetting fluid by a wetting one in a random porous medium is developed. The porous medium is modelled as a network of randomly sized unit cells of the constricted-tube type. Under creeping-flow conditions the problem is reduced to a system of linear equations, the solution of which gives the instantaneous pressures at the nodes and the corresponding flowrates through the unit cells. The pattern and rate of the displacement are obtained by assuming quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
0
6

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(117 citation statements)
references
References 11 publications
7
104
0
6
Order By: Relevance
“…The pore-scale two-pressure algorithm of DYPOSIT model provides the distribution of local capillary pressures at the interfaces of (the discontinuous) phases. This approach is much more efficient than the other pore-scale approaches for mobilization such as the search algorithm proposed by Ng and Payatakes (1980) or the definition of single pressure as proposed by Dias and Payatakes (1986). As shown schematically in Fig.…”
Section: Mobilization Of a Non-wetting Blobmentioning
confidence: 98%
“…The pore-scale two-pressure algorithm of DYPOSIT model provides the distribution of local capillary pressures at the interfaces of (the discontinuous) phases. This approach is much more efficient than the other pore-scale approaches for mobilization such as the search algorithm proposed by Ng and Payatakes (1980) or the definition of single pressure as proposed by Dias and Payatakes (1986). As shown schematically in Fig.…”
Section: Mobilization Of a Non-wetting Blobmentioning
confidence: 98%
“…When Ca is less than 10 −6 , the upper limit in most aquifers, experiments have shown that residual saturation is independent of Ca [Morrow and Chatzis, 1982]. However, models have indicated that viscous forces may affect blob configuration at capillary numbers as low as 10 −7 [Dias and Payatakes, 1986]. This suggests that the residual saturation and ganglia configuration may change in response to a change in flow velocity that may occur during aquifer remediation.…”
Section: Napl Distributionmentioning
confidence: 99%
“…The frontal dynamics can affect the oil recovery efficiency, as well as mass transport between NAPL/aqueous interface. The frontal structure can vary from compact to fingering pattern, depending on capillary number and viscosity ratio between invading and defending fluid [11,15,18,19]. In particular, at low injection rate, where viscous force can be neglected and capillary force dominates, capillary fingering is manifested.…”
Section: Introductionmentioning
confidence: 99%